« Guerre aux mots étrangers ! » : le protectionnisme et la censure dans la lexicographie portugaise du xxe siecle - Marques, Fernando Carmino (2016)
In the name of linguístic uniquenss, whose origin leads us to a more or less distant past, selective and paradigmatic, the Portuguese lexicologists, defenders of this opinion, do not hesitate in associating such uniquenss with superiority. These combatants, in the Lusitanian case, considcr the Portuguese language as superior to thc others, therefore possessing ali the resources to adapt the expression to the idea. There is a struggle with I no truce against foreign words that we have witnessed during the XX century.